Fundamentalisme dalam Agama Budha (Suatu Penelusuran Awal) - Abdul Syukur (Universitas Islam Indonesia, 2002)
The following article explains that it is very difficult to find the characteristics fundamentalism of Buddhism because the fundamentalism movement denotes the reaction to superficiality of spiritual values because of the modernization process. It invites the followers of religion back to the tenet of Holy Scripture. It is not only the superficiality of spiritual values but also the deconstruction of spiritual values themselves. If the fundamentalism emerges because of the disappointing of the secular modern society, the Buddhism at some countries tends to cooper ate with the regime of the state to support the modernization i.e. Srilangka and Thailand. Whereas at some states i.e. South Korea, Japan, Taiwan and Singapore the doctrine of Buddhism is understood from the modernism perspective, but, the spiritual values of the scripture complete the secular modem society. To save society with Holy Book indicates that the responsibilities of social, politic, and culture were regarded as Buddhism fundamentalism, in accord with social change that carried out by Soka Gakkai to overcome the frustration of society.